Adjunctive accelerated repetitive transcranial magnetic stimulation for older patients with depression: A systematic review - Zheng, Wei; Zhang, Xin-Yang; Xu, Rui; Huang, Xiong; Zheng, Ying-Jun; Huang, Xing-Bing; Li, Ze-Zhi; Chen, Huo-Di (Frontiers in Aging Neuroscience, 2022)
Objective: We performed this systemic review to investigate the therapeutic potential and safety of adjunctive accelerated repetitive transcranial magnetic stimulation (aTMS) for older patients with depression. Methods: We included published randomized clinical trials (RCTs) and observational studies targeting adjunctive aTMS for older patients with depression. Results: Two open-label self-controlled studies (n=29) fulfilled the criteria for inclusion. The included studies reported significant improvements in depressive symptoms from baseline to post-aTMS (all Ps<0.05). One study reported a dropout rate of 10.5% (2/19). Mild headache was the most common adverse reaction. Conclusion: The currently available evidence from two open-label self-controlled studies indicates that adjunctive aTMS is a safe and effective therapy for older patients with depression.